Regulation of AMPA receptors in spinal nociception - Lin Qing; Wu Zhiguo; Wu Jing; Wang Yun; Yue Yun; Fang Li (SAGE Publishing, 2010)
Abstract The functional properties of α-amino-3-hydroxy-5-methy-4-isoxazole propionate (AMPA) receptors in different brain regions, such as hippocampus and cerebellum, have been well studied in vitro and in vivo. The AMPA receptors present a unique characteristic in the mechanisms of subunit regulation during LTP (long-term potentiation) and LTD (long-term depression), which are involved in the trafficking, altered composition and phosphorylation of AMPA receptor subunits. Accumulated data have demonstrated that spinal AMPA receptors play a critical role in the mechanism of both acute and persistent pain. However, less is known about the biochemical regulation of AMPA receptor subunits in the spinal cord in response to painful stimuli. Recent studies have shown that some important regulatory processes, such as the trafficking of AMPA receptor subunit, subunit compositional changes, phosphorylation of AMPA receptor subunits, and their interaction with partner proteins may contribute to spinal nociceptive transmission. Of all these regulation processes, the phosphorylation of AMPA receptor subunits is the most important since it may trigger or affect other cellular processes. Therefore, these study results may suggest an effective strategy in developing novel analgesics targeting AMPA receptor subunit regulation that may be useful in treating persistent and chronic pain without unacceptable side effects in the clinics.